Kebijakan Pengembangan Kurikulum di Sekolah Dasar (Sebuah Tinjauan Kurikulum 2006 hingga Kebijakan Merdeka Belajar) - Agustinus Tanggu Daga (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2020)
Curriculum development is very important for curriculum developers in primary schools to improve the quality of educational processes and outcomes. The aim of this research is to find out how curriculum development in primary schools in the KBK, KTSP, Curriculum 2013, and the independent learning policy. This research method is descriptive qualitative. Literature review method is taken to collect the data from relevant resources. The research found out that curriculum development of the primary school occurs in the span of Indonesian history. The primary school curriculum is a competency-based curriculum designed in the KBK, KTSP, Curriculum 2013, and independent learning. The characteristics of the primary school curriculum in KTSP are a separated curriculum for grades IV-VI and thematic curriculum for grades I-III. The characteristics of the primary school curriculum in the 2013 curriculum are a cross curriculum or integrated curriculum for all grades with a scientific approach and authentic assessment. The primary school curriculum in independent learning needs to pay attention to curriculum simplification, national exams, simplifying lesson plans, the teaching profession. Meanwhile, the implementation of independent learning must include objectives, flexibility, and benefits of the curriculum.